Evaluation of anti-histaminic and bronchodilatory Activity of milk of equus africanus Asinus in rodents - J. ANBU; VANI. B. NANDIHALLI; RAMYA P.S; SUKANYA. K; HAJIRA BANU. H (International Journal of Pharma and Bio Sciences, 2016)
The Equus africanus asinus milk commonly known as donkey milk (DM) is often used as a substitute for breast milk, and as medicine for treating the child of delicate health, improving immunity, treatment of respiratory problems like cough, whooping cough and asthma in infants.The present study was therefore designed to evaluate the antihistaminic and bronchodilator activity of milk of Equus africanus asinus in rodents. Equus asinus milk was evaluated using histamine induced contractions on isolated ileum and tracheal chain preparations and histamine induced bronchoconstriction in Guinea pigs. The Equus asinus milk significantly inhibited histamine induced contraction of isolated guinea pig ileum and tracheal chain preparation and significantly protected the guinea pigs against histamine induced Bronchoconstriction as indicated by delay in the pre-convulsive dyspnoea time (PCT) following the exposure of histamine aerosol. The results suggested that Equus asinus milk has antihistaminic and bronchodilator activity and may prove beneficial effect in the management of asthma.